Impulsivity and substance misuse among Turkish people: Serial mediating effect of emotion dysregulation and general anxiety disorder - Tekin, Emine Gocet; Yilmaz, Fatma Betul; Satici, Seydi Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Substance misuse is an alarming issue worldwide that causes serious problems at both the individual and societal levels, placing a burden on public health systems and economies. Understanding the predictors of substance misuse may help prevent it and may be an adjunct to treatment. The present study examined the relationship among impulsivity, emotion dysregulation, generalized anxiety disorder, and substance misuse. A total of 462 participants age between 18 and 74 years (M = 33.67, SD = 12.91) from 49 cities across Turkiye, completed the measures of impulsivity, emotion dysregulation, generalized anxiety disorder, and substance misuse. Structural equation modeling indicated that impulsivity, emotion dysregulation, and generalized anxiety have a significant predictive role in substance misuse. Further, emotion dysregulation and generalized anxiety disorder mediate the relationship between impulsivity and substance misuse. These findings suggest that noticing and treating impulsivity, emotion dysregulation, and generalized anxiety may minimize the effects of substance misuse.
Keywords: Substance misuse; impulsivity; emotion; anxiety; structural equation modeling; NATIONAL EPIDEMIOLOGIC SURVEY; DRUG-USE; PROTECTIVE FACTORS; ALCOHOL; RISK; DIFFICULTIES; COMORBIDITY; MEDICATION; DRINKING; MOTIVES; Substance Abuse